Identification of potential prognostic biomarkers in vulval squamous cell carcinoma based on human papillomavirus infection Status-Analysis of GSE183454 - Ruxing Xi; Donghong Li; Shuanque Yang; Hui Zhang; Lijuan Hu; Xiaowei Wang; Guoqing Wang; Yan Wang (Taylor & Francis Group, 2023)
This study aimed to elucidate the differences in vulval squamous cell carcinomas (VSCC) based on the HPV infection status. The sequencing data GSE183454 which contains 23 VSCC samples based on its HPV infection status was obtained from the Gene Expression Omnibus (GEO) database. We comprehensively dissected the differences of genomic and tumour microenvironment (TME) immune cell infiltration landscapes between HPV + and HPV- VSCC. The potential molecular mechanisms of prognostic genes were explored by functional enrichment analysis. Five novel key molecules (SYCP2, SMC1B, RNF212, MAJIN and C14orf39) with significantly up-regulated expression in HPV + VSCC were identified while protein-protein interaction (PPI) networks were created upon Cytoscape software. Additionally, VSCC with up-regulated expression of these key molecules exhibited a significantly decreased TME immune cell infiltration. SYCP2 is overexpressed in HPV + VSCC and could be a candidate therapy target for further research.IMPACT STATEMENT What is already known on this subject? VSCC are characterised by two aetiological pathways. The former occurs in the background of lichen sclerosus, while the latter is related to HPV infection. VSCC most commonly arises from the non-HPV related pathway portends worse prognosis than VSCC derived from HPV infection. What do the results of this study add? Five key molecules are identified and significantly up-regulated in HPV + VSCC. In which, SYCP2 is overexpressed in HPV + VSCC and exhibited a significantly decreased TME immune cell infiltration. SYCP2 constant expression could be a potential biomarker of neoplasms associated with HPV and could be a candidate therapy target in VSCC especially HPV + VSCC for further research. What are the implications of these findings for clinical practice and/or further research? SYCP2 could be a candidate therapy target in VSCC especially with HPV + for further research.